Work Stress in Islam - Anida Yuliani; Maulida Maulida; Muhammad Rolly Fadlani; Maulida Ariani; Shanty Komalasari; Ceria Hermina (International Conference on Psychology and Education (ICPE), 2023)
Stress is a negative reaction that may occur in an individual due to the burden due to a large number of demands, constraints or opportunities, this study uses literature data and documentation or literal studies. Literature data that in some cases will be combined with existing reference sources. Work stress is a root or work stressor that results in individual reactions such as physiological, psychological, and behavioral. In conclusion from work stress in Islam, stress is a form of a dirty heart because of sins committed by man himself. The way to manage is to draw closer to Allah Almighty. namely by reading the Qur'an, thinking and praying in accordance with the sunnah taught by the Prophet Muhammad SAW.